Clinical characteristics of kidney transplant recipients admitted in the intensive care unit of the Hospital de Clínicas, Paraguay. - Pederzani, Marcelo; Fretes, Federico; Figueredo, Jessica; Avila, Silenne; Fontclara, Lorena; Daponte, Fernando; Saldivar, Agustín; Figueredo, Belinda (Medicina Clínica y Social, 2024)
Introduction: In December 1985, the first kidney transplant was performed at the Hospital de Clínicas. The multidisciplinary team worked in coordination to respond to the increasing needs of patients who required this therapy. The aim of this work was to characterize kidney transplant patients admitted to the Adult Intensive Care Department of the Hospital de Clínicas of the Faculty of Medical Sciences of the National University of Asunción. Methods: An observational, descriptive, retrospective cross-sectional study was made, with non-probabilistic sampling of consecutive cases. The records of all patients admitted to intensive care unit in the immediate postoperative period from January 2017 to December 2023 were used. Results: 74 kidney transplant patients were during the study period. The transplanted kidney proceeds from a cadaveric donor in 63.6%. Forty-eight were male (64,8%). The median age was 33 years. The main comorbidity of the recipient was arterial hypertension 79.7%. The prognostic score used was APACHE II, with a median of 12. The median number of days of hospitalization was 3. The 5.4% required mechanical respiratory assistance and the average number of days of ventilation was 9 (range: 2-19). Furosemide infusion was required in 48.6% of patients, vasodilators in 39,1% and 10.8% of vasopressors. Of the patients studied, 95.9% were on hemodialysis (n:71). Nine patients required dialysis sessions after transplantation. Doppler ultrasound of the transplanted kidney showed renal artery stenosis in 12.9%, with clinical repercussions in 2 patients, leading to transplantectomy in one of them. Discharge survival from intensive care was 100%. Two patients were readmitted in the mid-postoperative period with healthcare associated infections, who finally died. Conclusion: In Paraguay, kidney transplantation is a valid therapeutic option with good results and low complications for patients in the terminal stage of kidney disease.
Keywords: kidney transplant; intensive care; clinical characteristics